Perceptions of Class X MIPA Students of SMA N 1 Mejobo Regarding the Islamization Process in Kudus Regency - Fatmawati, Candra Dewi; Suharso, R (Indonesian Journal of History Education, 2016)
The aim of this research is (1) Historical learning on the subject of the Islamization process by Walisongo; (2) The perception of student SMA N 1 Mejobo to the Islamization process in Kudus regency; (3) The obstacles to historical learning on the subject of the Islamization process by Walisongo. This research is arranged in SMA N 1 Mejobo using a quantitative method. Informants are teachers and students of the school. Based on the analysis of the data of the research that can be expressed, (1) In learning historical learning about the process of Islamization by Walisongo, the teacher used the lecture method, discussion, and questions where students talk to teachers related to the subject; (2) Student have a positive perception to Sunan Kudus that is considered as Walisongo who spread Islam in Kudus. Students perceive Sunan Kudus as an Ulama who has a very high knowledge of Islam and a pioneer of Kudus as the town of Santry; (3) The obstacles in historical learning on the subject of the Islamization process by Walisongo is about time with the subject, which is very limited.